Late-stage modification of peptides and proteins at cysteine with diaryliodonium salts. Issue 42 (12th October 2021) - Byrne, Stephen A.; Bedding, Max J.; Corcilius, Leo; Ford, Daniel J.; Zhong, Yichen; Franck, Charlotte; Larance, Mark; Mackay, Joel P.; Payne, Richard J.
Abstract : New operationally simple platform for the chemoselective arylation of cysteine in peptides and proteins to access a variety of high value bioconjugates. Abstract : The modification of peptides and proteins has emerged as a powerful means to efficiently prepare high value bioconjugates for a range of applications in chemical biology and for the development of next-generation therapeutics. Herein, we report a novel method for the chemoselective late-stage modification of peptides and proteins at cysteine in aqueous buffer with suitably functionalised diaryliodonium salts, furnishing stable thioether-linked synthetic conjugates. The power of this new platform is showcased through the late-stage modification of the affibody zEGFR and the histone protein H2A.